Free Mobility with the EU and Immigration of North American Brains to Switzerland: What Consequences? - Dominique M. Gross (Swiss Journal of Economics and Statistics, 2012)
In 2002, Switzerland started to implement free mobility with the European Union and simultaneously immigration rules for citizens from the rest of the world became more stringent. Only skilled workers could be hired from third countries and employers had to give priority in hiring to Swiss and European skilled applicants. This paper shows that the new legislation has strongly adversely affected the size of high-skill immigration from North America. Also, incentives to leave those countries have changed as North Americans are more inclined to consider home professional networks and financial opportunities. The consequence is less geographical heterogeneity in immigrants which may decrease Swiss firms' ability to gain information about non-European markets and increase their entry cost into those markets.
Keywords: F22; J21; J61; 330; High-skill immigration; free mobility policy; Switzerland; North America; incentives